НОВЫЙ ПОДХОД К ОЦЕНКЕ ЭФФЕКТИВНОСТИ И БЕЗОПАСНОСТИ ЛЕКАРСТВЕННЫХ СРЕДСТВ ПРИ ПРОВЕДЕНИИ КЛИНИЧЕСКИХ ИССЛЕДОВАНИЙ У ИНФЕКЦИОННЫХ БОЛЬНЫХ - М. Л. Абрамович; А. А. Плоскирева (Архивъ внутренней медицины)
The article provides an overview of existing approaches to analysis of clinical and clinical-laboratory data in clinical studies in patients with infectious diseases and presents an innovative algorithm for assessment of efficacy and safety of medicinal products using hematological parameters.